Can Salivary Innate Immune Molecules Provide Clue on Taste Dysfunction in COVID-19? - Ermel, Aaron; Thyvalikakath, Thankam Paul; Foroud, Tatiana; Khan, Babar; Srinivasan, Mythily (Frontiers in Microbiology, 2021)
Emerging concerns following the severe acute respiratory syndrome coronavirus-2 (SARS-CoV2) pandemic are the long-term effects of coronavirus disease (COVID)-19. Dysgeusia in COVID-19 is supported by the abundant expression of the entry receptor, angiotensin converting enzyme-2 (Ace2), in oral mucosa. The invading virus perturbs the commensal biofilm and regulate the host responses that permit or suppress viral infection. We correlated the microbial recognition receptors and soluble ACE2 (sAce2) with the SARS-CoV2 measures in saliva of COVID-19 patients. Data indicate that the toll like receptor-4, peptidoglycan recognition protein and sACE2 are elevated in COVID-19 saliva and correlate moderately with the viral load.